How tobacco companies use the revolving door between government and industry to influence policymaking: an Australian case study - Christina Watts; Melissa Jones; Kylie Lindorff; Becky Freeman (Sax Institute, 2023)
Objectives and importance of the study: The study investigates and documents how tobacco companies are using the revolving door between government and industry as a tactic to try to influence public health policymaking in Australia. This is the first Australian study to systematically investigate the revolving door tactic in tobacco lobbying and highlights the importance of strengthening integrity and transparency legislation and oversight bodies to eliminate the political influence of tobacco companies in Australia. Study type: Mixed-methods including non-experimental descriptive and exploratory case studies. Methods: To build a picture of tobacco lobbying through the revolving door in Australia, data was triangulated from multiple publicly available sources: 1) Australian federal, state and territory government lobbyist registers, 2) the online social networking platform, LinkedIn; and 3) Australian news media reports. Results: Tobacco companies lobby the Australian government using 'in-house' employees, lobbyists working in firms acting on their behalf, and third-party allies with common interests. Almost half (48%) of internal tobacco company lobbyists had held positions in the Australian government (state, territory and/or federal) before or after working in the tobacco industry. Likewise, 55% of lobbyists acting on behalf of tobacco companies had held government positions before or after working as a lobbyist. In-house tobacco industry lobbyists, as well as those working on behalf of tobacco companies within lobbying firms, were found to have held senior governmental positions, such as a Member of Parliament (MP) or Senator, chief or deputy chief of staff, or senior advisor in a ministerial office, and many had moved into or out of government within 1 year of working for a tobacco company (56%) or as a lobbyist (48%). Conclusions: Tobacco companies are strategically using the revolving door between the government and the tobacco industry as a key political lobbying mechanism to try to influence public health policy in Australia.